A Prototype of Biaxial Extensometer to Measure Human Skin Elasticity - L. Dzan; Z. Lochman; L. Čapek; A. Lufinka (Česká Stomatologie a Praktické Zubní Lékařství, 2010)
In our article we would like to present the results of joint research carried out at the Regional Hospital in Liberec and the Technical University of Liberec. The aim of this research was to design a prototype for biaxial measuring of mechanical properties of the human skin in vivo. Biaxial application of the load will allow for the evaluation of specific human skin parameters which cannot be determined during a uniaxial tensile test because of the skin anisotropy. This prototype was called "BiEx" (biaxial extensometer).